2015
DOI: 10.18632/oncotarget.4082
|View full text |Cite
|
Sign up to set email alerts
|

F-box protein FBXO22 mediates polyubiquitination and degradation of KLF4 to promote hepatocellular carcinoma progression

Abstract: Kruppel-like factor 4 (KLF4), a member of the KLF family of transcription factors, has been considered as a crucial tumor suppressor in hepatocellular carcinoma (HCC). Using affinity purifications and mass spectrometry, we identified FBXO22, Cullin1 and SKP1 as interacting proteins of KLF4. We demonstrate that F-box only protein 22 (FBXO22) interacts with and thereby destabilizes KLF4 via polyubiquitination. As a result, FBXO22 could promote HCC cells proliferation both in vitro and in vivo. However, KLF4 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
1
34
1
Order By: Relevance
“…Thus, we conclude that FBXO32 is a liable E3 ligase that mediates KLF4 turnover in breast cancer cells. Interestingly, a recent study reported that FBXO22 degrades KLF4 in hepatocellular carcinoma, 42 whereas in our situation knockdown of FBXO22 had negligible effect on KLF4 protein level.…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, we conclude that FBXO32 is a liable E3 ligase that mediates KLF4 turnover in breast cancer cells. Interestingly, a recent study reported that FBXO22 degrades KLF4 in hepatocellular carcinoma, 42 whereas in our situation knockdown of FBXO22 had negligible effect on KLF4 protein level.…”
Section: Discussioncontrasting
confidence: 83%
“…It should be noted that Johmura et al (31) have observed proliferative defects in immortalized retina pigmented epithelial cells depleted of FBXO22 and in FBXO22 −/− mouse epithelial fibroblasts. Similar growth defects were reported in human liver cancer HepG2 cells treated with shRNA against FBXO22 (39). In addition, overexpression of FBXO22 accelerated cell proliferation and colony formation in a number of breast cancer cells (40).…”
Section: Low Fbxo22 Expression Is Correlated With Worse Survival In Hsupporting
confidence: 76%
“…In hepatocellular carcinoma (HCC) cells, SCF(Fbxo22) can ubiquitinate KLF4 causing its degradation, promoting cell proliferation, anchorage independence, and invasiveness. These phenotypes and the increased Fbxo22 levels found in patient samples suggest a TSG role for KLF4 in this cell type (71).…”
Section: Sustaining Proliferation By Blocking Differentiationmentioning
confidence: 84%